Altitude bibliography
This altitude resource page of the High Altitude Sports Training Complex of the Northern Arizona University is not intended to present an exhaustive list of altitude-related abstracts and articles; rather its purpose is to feature a selection of such sources for use with certain research projects, literature reviews, etc. as well as provide a generalized source for those interested in altitude-related research and training protocols.